"It's not lupus". A placental site trophoblastic tumor presenting as a lupus-like paraneoplastic syndrome. A grand round case. (March 2021) - van der Lely, Sarah J; Boorsma, Jeffrey; Hilhorst, Marc; Kers, Jesper; Roelofs, Joris; Jakulj, Lily; van Onna, Marieke
Introduction: Placental site trophoblastic tumor (PSTT) is a rare subtype of gestational trophoblastic disease. Association of PSTT and nephrotic syndrome is exceedingly rare and has been described in 8 cases thus far. In all cases hysterectomy was performed within months after onset of symptoms, leading to immediate remission of nephrotic syndrome, except for one patient who died of complications of PSTT.Case: We describe the history of a woman in which PSTT was discovered years after onset of nephrotic syndrome. Kidney biopsy revealed lupus-like mesangiocapillary nephritis and over time the patient developed additional symptoms mimicking systemic lupus erythematosus (SLE).Discussion: We provide an overview of the literature on this clinical entity and elaborate on its pathophysiology. In addition, we reflect on the phenomenon of anchoring bias, that led physicians to assume the patient had SLE without questioning this diagnosis in the light of the unexplained finding of increased tumor markers.